Gene expression profile in leucocytes of type 2 diabetic subjects - Kaviarasan, S.; Muniandy, S.; Qvist, R.; Ismail, I.S. (2009)
Communication between insulin target tissues and beta-cells initiate compensatory responses which increase insulin production. Correlated changes, in gene expression between tissues, can provide evidence for such intercellular communication. We profiled gene expression studies in Type 2 diabetic subjects to unveil the mechanistic factors involved. Our results showed that genes involved in carbohydrate, lipid and amino acid metabolism pathways, glycan of biosynthesis, metabolism of cofactors and vitamin pathways, ubiquitin-mediated proteolysis, signal transduction pathways, neuroactive ligand receptor interaction were upregulated in diabetes compared to healthy subjects. In contrast, genes involved in cell adhesion, cytokine-cytokine receptor interaction, insulin signaling, PPAR signaling pathways were downregulated in subjects with type 2 diabetes mellitus (T2DM). 2 -microglobulin, a MHC class I molecule was strongly downregulated in diabetic subjects. Further, genes involved in inflammatory pathway are differentially expressed in subjects with T2DM. Hence, it was evident that genes concerned with pathways of carbohydrate, lipid and amino acid metabolism, neuronal function and inflammation play a significant role in the pathobiology of T2DM.